Diam dan Luka: Pengalaman Komunikasi Remaja Pelaku Self-Harm di Kota Pekanbaru - Aidil Fitrian; Welly Wirman; Ringgo Eldapi Yozani (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to explore the communication experiences of adolescents engaging in self-harm in Pekanbaru City using a qualitative phenomenological approach. Data were collected through in-depth interviews with six participants selected using a snowball technique. The findings reveal that communication experiences are formed within four main contexts: family, peers, romantic partners, and community. Supportive, open, and empathetic communication both verbal and nonverbal, emerges as a protective factor that enhances emotional stability and reduces self-harm tendencies. In contrast, negative communication such as verbal abuse, emotional neglect, social exclusion, and abusive relationships intensifies feelings of isolation, low self-worth, and psychological vulnerability. Additionally, communities serve as alternative spaces that can support recovery, although they may also present risks of social rejection. Thus, the quality of interpersonal communication plays a crucial role in shaping relational experiences and the dynamics of self-harm among adolescents.